Infusions of Nerve Growth Factor Into the Developing Frontal Cortex Leads to Deficits in Behavioral Flexibility and Increased Perseverance - Desai, Sagar J (Schizophr Bull, 2018)
In the pursuit of further establishing a neurodevelopmental animal model to investigate the mechanisms underlying impaired executive function, a core and severely debilitating symptom of schizophrenia, we sought to characterize the deficits in behavioral flexibility in adult rats following neonatal infusions of nerve growth factor (NGF) into the medial part of the developing frontal cortex. Our previous studies using this neonatal frontal cortical lesion model have shown that it leads to adult-onset positive and negative symptom-like features, and several neuropathological abnormalities of schizophrenia. In the present study, we used operant conditioning-based paradigms to investigate set-shifting ability and reversal learning performance in adult rats that received infusions of NGF into the developing frontal cortex on post-natal day 1. NGF-infusion caused apoptosis of cells in the subplate layer. Adult rats that received neonatal infusions of NGF showed decreased grey matter thickness, and decreased levels of parvalbumin in prelimbic and infralimbic areas of the medial prefrontal cortex (mPFC). NGF-treated rats had difficulty completing the set-shifting and reversal learning tasks due to increased perseverance (ie, a failure to disengage from the previously-learned strategy once the rule contingencies were changed) compared to the control group. Collectively, these results identify the crucial role of the frontal cortical subplate layer in the structural and functional development of the mPFC relevant to schizophrenia. Furthermore, the present findings substantially advance the face and construct validity of this putative preclinical model of schizophrenia based on developmental disruption of the frontal cortical subplate.